A method for project portfolio risk assessment considering risk interdependencies – a network perspective - Mican, Camilo (2022)
Project portfolios represent the bridge between projects and strategy. However, the final results may not be as expected because materialization of risk factors. Hence, literature has acknowledged project portfolio risk assessment as an element of the project portfolio risk management, being the element that provides information on the importance of risk factors. For that, some specific characteristics should be considered, such as risk interdependency influence and the risk factors impact over portfolio higher levels. Thus, this study is focused on the development of a method for project portfolio risk assessment that considers both risk factor interdependencies and their impact on the strategic objectives as a network. In addition, the method also allows incorporating both risk factors derived from projects and derived at project portfolio level. A representative example is provided to illustrate the proposed method.